Effect of silicon sources on rice diseases and yield in the State of Tocantins, Brazil - Gil Rodrigues dos Santos (Acta Scientiarum. Agronomy, 2011)
The intensity of rice diseases in regions with poor levels of silicates (Si) in the soil, together with high control costs, can make the cultivation of rice unfeasible. Surprisingly, there are scarce research data available regarding the influence of Si on rice diseases in tropical lowland regions. Therefore, the aim of this study is to determine the effect of three silicon sources on rice yield and disease management. Three experiments were carried out from December 2005 to April 2006 at an experimental field area located in Formoso do Araguaia, Tocantins state, Brazil. Each experiment consisted of one silicon source (powder, granular or liquid) and the treatments consisted of six Si doses. All the treatments were performed in a completely randomized block design. The data presented in this study provide evidence that Si applications in Si-deficient soils of lowland regions, depending on the application source, dose and disease intensity, can decrease the severity of brown spot and the incidence of panicle blast. Calcium silicate effectively reduced the brown spot and the panicle blast, which resulted in an increased rice yield. In contrast, Ca and Mg silicate and potassium silicate did not show an efficient control of rice diseases nor an increase in productivity.